THE INFLUENCE OF INDEPENDENT BOARD OF COMMISSIONERS AND ENVIRONMENTAL DISCLOSURE ON FIRM VALUE WITH FINANCIAL PERFORMANCE AS A MODERATING VARIABLE IN CONSUMER GOODS SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE IN 2021-2024. - Moza Safira; Fahmi Natigor Nasution; Ibnu Austrindanney Sina Azhar (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
This study aims to analyze the influence of independent board of commissioners and environmental disclosure on firm value with financial performance as a moderating variable in consumer goods sector companies listed on the Indonesia Stock Exchange in 2021-2024. This study employs a quantitative approach. The research population consists of consumer goods sector companies listed on the Indonesia Stock Exchange in 2021-2024, with a sample of 22 companies selected using purposive sampling technique, resulting in 88 observations during the research period. The type of data used is secondary data, and the data analysis techniques employed are panel data regression and Moderated Regression Analysis (MRA). The research findings indicate that an independent board of commissioners has a positive and significant effect on firm value, environmental disclosure has a negative and significant effect on firm value, and financial performance significantly moderates and strengthens the influence of an independent board of commissioners on firm value.